2020
DOI: 10.1007/s41062-020-00306-x
|View full text |Cite
|
Sign up to set email alerts
|

In-plane behavior of various brick bonds in masonry walls

Abstract: An analytical investigation is carried out to evaluate the influence of brick bond types in in-plane behavior of brick masonry. Header, Stretcher, and English bonds are chosen for numerical simulation for in-plane loading. For numerical modeling, simplified micro-modeling approach is adopted using plasticity-based constitutive models. Three-dimensional nonlinear simulations for the brick bonds for various aspect ratios and pre-compression are carried out in this study. The lateral in-plane displacement control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In (Taguchi and Cuadra 2015) a comparison between english and flemish masonry walls has been carried out demonstrating that a larger volume of joints in a flemish wall would lead to a weaker structure in comparison with an english bond masonry wall. Furthermore, (Shrestha et al 2020) implemented a micro-modelling numerical approach to simulate the structural behaviour of masonry panels composed with different bond types and concluded that the elastic response of the panels was not influenced by the bond type, only the ultimate failure load was affected by this parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In (Taguchi and Cuadra 2015) a comparison between english and flemish masonry walls has been carried out demonstrating that a larger volume of joints in a flemish wall would lead to a weaker structure in comparison with an english bond masonry wall. Furthermore, (Shrestha et al 2020) implemented a micro-modelling numerical approach to simulate the structural behaviour of masonry panels composed with different bond types and concluded that the elastic response of the panels was not influenced by the bond type, only the ultimate failure load was affected by this parameter.…”
Section: Introductionmentioning
confidence: 99%